2019
DOI: 10.1016/j.ppnp.2019.103715
|View full text |Cite
|
Sign up to set email alerts
|

Hadron matter in neutron stars in view of gravitational wave observations

Abstract: In this review we highlight a few physical properties of neutron stars and their theoretical treatment inasmuch as they can be useful for nuclear and particle physicists concerned with matter at finite density (and newly, temperature). Conversely, we lay out some of the hadron physics necessary to test General Relativity with binary mergers including at least one neutron star, in view of the event GW170817: neutron stars and their mergers reach the highest matter densities known, offering access to the matter … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 289 publications
0
15
0
Order By: Relevance
“…The models introduced so far can be further generalized to a family of theories encompassing those defined via scalars built out of the (symmetrized) Ricci tensor 44 and its contractions with the metric. This family of metric-affine theories is known as Ricci-Based Gravity theories (RBGs) [57].…”
Section: Ricci-based Gravity Theoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…The models introduced so far can be further generalized to a family of theories encompassing those defined via scalars built out of the (symmetrized) Ricci tensor 44 and its contractions with the metric. This family of metric-affine theories is known as Ricci-Based Gravity theories (RBGs) [57].…”
Section: Ricci-based Gravity Theoriesmentioning
confidence: 99%
“…Unfortunately, simultaneous measurements of mass and radius for the same neutron star, which would allow to place constraints upon the EOS, are hard to achieve [30,31]. There are further observational weapons available to this challenge, such as the measurement of neutron stars' moment of inertia [32], as well as the analysis of gravitational wave and gamma ray burst data from binary neutron star mergers [33,34,35,36], which allows to place constraints on tidal deformability [37] (and to infer the moment of inertia [38]), on the EOS at supranuclear densities [39,40,41,42,43] (for a recent review see [44]) and on further properties [45]. Conversely, the combined measurements of radii and tidal deformability can also place constraints on the EOS [46].…”
Section: Introductionmentioning
confidence: 99%
“…This is valid for any and (44) is to be substituted for y when evaluating Λ from (42). A number of studies have computed examples of Λ for a wide range of EOS models and delineated interpretations of its physics content such as symmetry energy, phase transitions, and multi-body interactions [16,25,29,30,59,74,86,112,113,121,129,168,[204][205][206]213,223,239,246,254,267,270,282,293,305,307,319,328,329,[343][344][345][346][347][348][349][350][351][353][354][355]362,363,365,378,385,402,…”
Section: Calculation Of Tidal Deformability In Grmentioning
confidence: 99%
“…Oertel et al [3] reviewed comprehensively the status of our knowledge about the EoS of neutron stars (NSs) and core-collapse supernovae (CCSN) before the observation of gravitational waves (GW), detailing many theoretical methods and astrophysical and terrestrial data needed for constructing an EoS model and constraining its parameters. A more recent review [4], focussed on a wide range of aspects of the GW observation, and related them to a hybrid EoS, built on the chiral effective field theory (χEFT) at low density and the perturbative QCD (pQCD) at high densities. The recent status of the research of the EoS of neutron stars can be found in [5].…”
Section: The Equation Of Statementioning
confidence: 99%